2002
DOI: 10.1146/annurev.arplant.53.100301.135251
|View full text |Cite
|
Sign up to set email alerts
|

THECOMPLEXFATE OFα-KETOACIDS

Abstract: Plant cells are unique in that they contain four species of alpha-ketoacid dehydrogenase complex: plastidial pyruvate dehydrogenase, mitochondrial pyruvate dehydrogenase, alpha-ketoglutarate (2-oxoglutarate) dehydrogenase, and branched-chain alpha-ketoacid dehydrogenase. All complexes include multiple copies of three components: an alpha-ketoacid dehydrogenase/decarboxylase, a dihydrolipoyl acyltransferase, and a dihydrolipoyl dehydrogenase. The mitochondrial pyruvate dehydrogenase complex additionally include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
151
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(153 citation statements)
references
References 85 publications
2
151
0
Order By: Relevance
“…First, we have recently shown that a total knockout of GDC is lethal even in nonphotorespiratory conditions, indicating that GDC fulfils a nonreplaceable function in vital metabolic processes other than photorespiration (Engel et al, 2007). Second, in addition to H protein, other mitochondrial proteins of strategic importance, mainly the E2 subunits of the a-ketoacid dehydrogenase complexes PDH and KGDH, also require lipoylation for their activity (Mooney et al, 2002;Taylor et al, 2004). Therefore, the observed features of mtkas mutants indicate significant residual activities of all three multienzyme complexes and point to the possibility that mitochondrial protein lipoylation may not be exclusively dependent on mtKAS.…”
Section: Effects On Photosynthesis and Leaf Amino Acid Contentmentioning
confidence: 99%
“…First, we have recently shown that a total knockout of GDC is lethal even in nonphotorespiratory conditions, indicating that GDC fulfils a nonreplaceable function in vital metabolic processes other than photorespiration (Engel et al, 2007). Second, in addition to H protein, other mitochondrial proteins of strategic importance, mainly the E2 subunits of the a-ketoacid dehydrogenase complexes PDH and KGDH, also require lipoylation for their activity (Mooney et al, 2002;Taylor et al, 2004). Therefore, the observed features of mtkas mutants indicate significant residual activities of all three multienzyme complexes and point to the possibility that mitochondrial protein lipoylation may not be exclusively dependent on mtKAS.…”
Section: Effects On Photosynthesis and Leaf Amino Acid Contentmentioning
confidence: 99%
“…These accessory proteins are apparently lacking in bacterial PDH where regulation occurs through allosteric mechanisms and product inhibition (54). The E1 protein of PDH from mitochondria and from Gram-positive bacteria is composed of two different subunits (E1␣ and E1␤), which form an ␣ 2 ␤ 2 heterotetramer (52,55). In contrast, the E1 protein in many Gram-negative bacteria is organized as a homodimer of translationally fused ␣ and ␤ subunits ((␣␤) 2 ) (54,55).…”
Section: Proteomic Studies Reveal An Anaerobic Response In Euglenamentioning
confidence: 99%
“…The plastid form PDCs provide acetyl-CoA and NADH for fatty acid biosynthesis (Lernmark and Gardestrom 1994), whereas the mitochondria form PDCs are important in controlling the entry of carbon into the TCA cycle (Camp and Randall 1985). Most mitochondrial and plastidial proteins, including the subunits of the PDCs, are encoded within the nuclear genome of land plants, synthesized in the cytoplasm and then post-translationally imported into the organelles (Mooney et al 2002). In the present study, CsPDC-E1α was isolated from C. sinensis and phylogenetic analysis of plant PDC-E1α proteins revealed that CsPDC-E1α shares a high degree of homology with PhPDC-E1α (Petunia x hybrida) and VvPDC-E1α (Fig.…”
Section: Discussionmentioning
confidence: 99%